Hand Sanitizer dari Daun Mangga sebagai Upaya Menekan Penyebaran Pandemi Covid-19 di Wilayah Jebres dan Polokarto - Maria Ulfa; Ida Setiarini; Ika Uswatun Hasanah; Kusumandari Kusumandari; Teguh Endah Saraswati (Universitas Mathla'ul Anwar Banten, 2021)
HAND SANITIZER FROM MANGO LEAVES AS AN EFFORT TO SUPPRESS THE SPREAD OF THE COVID-19 PANDEMIC IN THE JEBRES AND POLOKARTO REGIONS. Covid-19 is an international pandemic that still has many victims. The UNS Campus area is a vulnerable area because apart from being public, there are also many residents who live around the campus which can be a medium for spreading the virus. The implementation of the health protocol, one of which is washing hands with running water or using a hand sanitizer, is one of the preventive measures to prevent the spread of the virus. Synthetic hand sanitizers have a lot of impact, especially for people who are sensitive to chemicals such as alcohol or synthetic disinfectants. On the other hand, the use of hand sanitizers has an important position to suppress the spread of the virus because it has the power to deactivate proteins from the Covid-19 spike section. Therefore, a breakthrough is needed to make natural hand sanitizers that are cheaper and have long-term sustainability. One of the natural ingredients that have a high antibacterial content is mango leaves. Various studies have stated that the tannin content of mango leaves is around 1.0 mg/g capable of deactivating bacteria and viruses. Unfortunately, so far, mango leaves are not used much except as fertilizer and more is wasted as garbage. In addition, the long pandemic period has caused the community not to have large reserves of hand sanitizers for their daily needs. Therefore, in this community service, training on the manufacture of hand sanitizers was carried out in the area around the UNS campus to provide skills to the community in procuring hand sanitizers independently from the plants around them as well as providing stock of natural hand sanitizers for people who are sensitive to chemicals.